UTILIZING BUSINESS GAME FOR IMPROVING STUDENTS’ SPEAKING PROFICIENCY IN ECONOMICS FACULTY - Rina Sari; Noverita Wahyuningsih (Universitas Islam Lamongan, 2019)
In the field of English teaching and learning, many English teachers see that teaching English for Specific Purposes (ESP) is relatively very challenging and thus demands a great deal of creativity to manage classroom activities. This paper aims at describing the use of ILO-SIYB Business Game, a business simulation, for improving students’ speaking proficiency. This study employed classroom action research, which was administered to find out how the ILO-SIYB Business Game can help improving speaking proficiency of students in Economics Faculty of Maulana Malik Ibrahim State Islamic University of Malang, Indonesia. The result of the study showed that the use of ILO-SIYB Business Game could improve students’ speaking proficiency, in terms of several aspects covering fluency, accuracy, and enjoyment in class. Therefore, the game is recommended to be used in ESP classes, especially to students of Economics Faculty. Key words: ILO-SIYB business game, Speaking proficiency, Economic faculty